An Efficient and Green Synthesis of Benzylidene-2-N-(carbothioamido)-6-oxo-1,2,5,6-tetrahydro-1-NH-1,2,4-triazine Derivatives and their Antibacterial Activity Evaluation - Anitha Rani, V.; Bharathi Kumari, Y. (Asian Journal of Chemistry, 2014)
An efficient and green synthesis of (Z)-3-allkyl-5(benzylidene/substituted benzylidene)-2N- (carbothioamido)-6-oxo-1,2,5,6-tetrahydro-1-NH-1,2,4-triazine derivatives have been developed in good yields and tested for their antibacterial activities against Escherichia coli, Providencia aeruginosa, Pseudomonas azotogensis and Baccilus subtillis. Some of the synthesized compounds possess good activity against Escherichia coli and Baccilus subtillis compared to standard drug streptomycin.